2015
DOI: 10.11113/jt.v77.6720
|View full text |Cite
|
Sign up to set email alerts
|

Illumina®truseq® vs Nebnext® Small Rna Library Preparation Kit for Mirna Profiling in Persicaria Minor: Which Better?

Abstract: In plants, a group of non-coding small RNA (sRNA) has been provento be an important player in regulating gene expression that can govern network of genetic systems. The two major classes of sRNA which are very extensively studied through deep sequencing, microRNA (miRNA) and small-interfering RNA (siRNA) classes, are well documented. However, the isolation method of sRNA differs depending on the type of sample. Here, we demonstrate the miRNA library preparation using two different Small RNA Library preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The integrity of the RNA was assessed by running a 1% agarose gel and Bioanalyzer analysis (Agilent 2100 Bioanalyzer, USA). A small RNA library was constructed using the NEBNext Small RNA Library preparation kit as reported by a previous study [22]. Then, the libraries were sent to Universiti Malaya, Malaysia for sequencing using an Illumina HiSeq 2500™ in Rapid Run mode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrity of the RNA was assessed by running a 1% agarose gel and Bioanalyzer analysis (Agilent 2100 Bioanalyzer, USA). A small RNA library was constructed using the NEBNext Small RNA Library preparation kit as reported by a previous study [22]. Then, the libraries were sent to Universiti Malaya, Malaysia for sequencing using an Illumina HiSeq 2500™ in Rapid Run mode.…”
Section: Methodsmentioning
confidence: 99%
“…Next generation sequencing (NGS), a more recent approach, has also been introduced for miRNA study, and this method has been found to be more advanced and efficient. This approach can detect low copy number miRNAs at levels of one transcript per million [21, 22]. To date, a total of 38,589 miRNAs from animals, plants, and viruses have been discovered and deposited in public miRNA databases [23].…”
Section: Introductionmentioning
confidence: 99%
“…DNA libraries for sequencing were prepared with three kinds of preparation kits; TruSeq Small RNA Library Prep Kit (TruSeq, Illumina, Inc.) [19], NEBNext Multiplex Small RNA Library Prep Set for Illumina (NEBNext, New England BioLabs Inc.) and SMARTer1 micro-RNA-Seq Kit (SMARTer, Takara Bio USA, Inc.) [20][21][22]. In general, manufacturer's protocols were used except for the final size selection step.…”
Section: Sequencingmentioning
confidence: 99%